Comparison of Transbronchial and Cryobiopsies in Evaluation of Diffuse Parenchymal Lung Disease. Issue 1 (January 2016) - Ramaswamy, Anuradha; Homer, Robert; Killam, Jonathan; Pisani, Margaret A.; Murphy, Terrence E.; Araujo, Katy; Puchalski, Jonathan
Abstract : Background: Diffuse parenchymal lung diseases (DPLDs) are common. An accurate diagnosis is essential due to differences in etiology, clinicopathologic features, therapeutic options, and prognosis. Transbronchial lung biopsies (TBLBs) are often limited by small specimen size, crush artifact, and other factors. Transbronchial lung cryobiopsies (TBLCs) are under investigation to overcome these limitations. Methods: We conducted a retrospective study of 56 patients in a single, tertiary-care academic center to compare the yield of both techniques when performed in the same patient. Patients underwent flexible bronchoscopy using moderate sedation with TBLB followed by TBLC in the most radiographically abnormal areas. Clinical data and postprocedural outcomes were reviewed, with a final diagnosis made utilizing a multidisciplinary approach. Results: The mean age of patients was 60 years and 54% were male. Comorbidities included COPD (14%) and prior malignancy (48%). The number of TBLB specimens ranged from 1 to 10 per patient (mean 4) and size varied from 0.1 to 0.8 cm. The number of TBLC specimens ranged from 1 to 4 per patient (mean 2) and size ranged from 0.4 to 2.6 cm. Both techniques provided the same diagnosis in 26 patients (46%). An additional 11 (20%) patients had a diagnosis established by adding TBLC to TBLB. Compared with TBLB, TBLC had a higher diagnostic yield in patients with hypersensitivity pneumonitis and interstitial lung disease. Only 2 patients required video-assisted thoracoscopic surgery to establish a diagnosis. Complications included pneumothorax (20%) and massive hemoptysis (2%). Conclusion: TBLC used with TBLB can improve the diagnostic yield of flexible bronchoscopy in patients with DPLD.